INVESTMENT ATTRACTION, COMPETITION AND GROWTH; THEORETICAL PERSPECTIVE IN THE CONTEXT OF AFRICA - SENZU, Emmanuel Tweneboah (Theoretical and Practical Research in Economic Fields; Vol 9 No 1 (2018): TPREF, Volume IX, Issue 1(17), Summer 2018DO - 10.14505/tpref.v9.1(17).10, 2018)
Examination in both theoretical and empirical prospective of the Capital market, deduce that the major indicators of modern economic growth, depends on the extent of economic financialization, commonly defined as capital stock, industrialization and Technological Advancement. The focus of this paper is to theorize investment attraction mechanism for a national economy in a global competitive arena, taking a posteriori perspective of Africa politico-economic climate.